Chinese parents' willingness to vaccinate their children against COVID-19: A systematic review and meta-analysis - Ma, Yundi; Ren, Jingjing; Zheng, Yang; Cai, Dongping; Li, Shuai; Li, Yangni (Frontiers in Public Health, 2022)
Background: To evaluate Chinese parents' willingness to vaccinate their children against COVID-19, identify its predictors, and provide a reference for raising the COVID-19 vaccination rate for children. Method: PubMed, Cochrane Library, Embase, and the databases in Chinese, including CNKI, WanFang, VIP, CBM, were searched from December 2019 to June 2022, and citation tracking was used to identify relevant studies. To calculate the rate with 95% confidence intervals (CI), a random-effects model was used. To explore sources of heterogeneity, sensitivity analysis and subgroup analysis were conducted. This analysis was registered on PROSPERO (CRD42022346866) and reported in compliance with the PRISMA guidelines. Result: Overall, 80 studies were screened, and 13 studies with 47994 parents were included after removing duplicates and excluding 19 studies that did not meet the selection criteria by title, abstract and full-text screening. The pooled willingness rate of Chinese parents to vaccinate their children against COVID-19 was 70.0% (95% CI: 62.0~78.0%). Level of education, perceived susceptibility of children infected with COVID-19, and parental attitudes toward vaccination (such as perceived efficacy and safety of the COVID-19 vaccines, parental willingness to vaccinate themselves, parental vaccination hesitancy, and the history of children's vaccination against influenza) were the main predictors of parents' intention to vaccinate their children. Conclusion: Chinese parents' willingness to vaccinate their children against COVID-19 is moderate, and factors including parental education level, perceived susceptibility of children infected with COVID-19, and parental attitudes toward vaccination affect this decision. Fully identifying these factors and their mechanism will be essential to further raise the willingness rate.